Peran Kebidanan Komunitas Dalam Penurunan Angka Kematian Ibu Dan Angka Kematian Bayi Menuju Indonesia Emas 2045 - Siswanto Pabidang (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: The health of mothers and babies was the main priority in determining the quality of human resources (HR) by reducing maternal and child mortality rates. Therefore, the role of community midwifery in achieving the goal of reducing maternal and child mortality is very important. The aim of research was among other things, to examine the legal basis for the role of community midwifery in reducing maternal and infant mortality (IMR) and to determine service strategies in community midwifery.Method: This research was qualitative research with a narrative literature review method with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analysis) method and the final search results were 5 journals.Result: The research results showed that the legal basis for the role of midwives in dealing with MMR and IMR is explained by Health Law Number 17 of 2023 concerning Health or Health Law Number 36 of 2014 concerning Health Workers as well as Law 4 of 2019 concerning Midwifery. The role of midwives in reducing MMR and IMR includes providing sustainable services focusing on preventive aspects through health education and counseling, health promotion, assisting with normal childbirth based on partnerships and women's empowerment as well as carrying out early detection in cases of maternal and child death. The service strategy of community midwifery in improving maternal and child health is an educational approach, good communication and community empowermentKeywords: midwives, death, community, roles and strategies.